Superior spatial resolution in confocal X-ray techniques using collimating channel array optics: elemental mapping and speciation in archaeological human bone. Issue 3 (31st January 2017) - Choudhury, S.; Agyeman-Budu, D. N.; Woll, A. R.; Swanston, T.; Varney, T. L.; Cooper, D. M. L.; Hallin, E.; George, G. N.; Pickering, I. J.; Coulthard, I.
Abstract : A novel X-ray collimating optic enables improved spatial resolution in confocal X-ray fluorescence imaging and X-ray absorption spectroscopy. Abstract : Confocal X-ray fluorescence imaging (CXFI) and confocal X-ray absorption spectroscopy (CXAS) respectively enable the study of three dimensionally resolved localization and speciation of elements. Applied to a thick sample, essentially any volume element of interest within the X-ray fluorescence escape depth can be examined without the need for physical thin sectioning. To date, X-ray confocal detection generally has employed a polycapillary optic in front of the detector to collect fluorescence from the probe volume formed at the intersection of its focus with the incident microfocus beam. This work demonstrates the capability of a novel Collimating Channel Array (CCA) optic in providing an improved and essentially energy independent depth resolution approaching 2 μm. By presenting a comparison of elemental maps of archaeological bone collected without confocal detection, and with polycapillary- and CCA-based confocal detection, this study highlights the strengths and limitations of each mode. Unlike the polycapillary, the CCA shows similar spatial resolution in maps for both low (Ca) and high (Pb and Sr) energy X-ray fluorescence, thus illustrating the energy independent nature of the CCA optic resolution. While superior spatial resolution is demonstrated for all of these elements, the most significant improvement is observed for Ca, demonstrating the advantage of employing the CCA optic in examining light elements. In addition to CXFI, this configuration also enables the collection of Pb L3 CXAS data from micro-volumes with dimensions comparable to bone microstructures of interest. Our CXAS result, which represents the first CCA-based biological CXAS, demonstrates the ability of CCA optics to collect site specific spectroscopic information. The demonstrated combination of site-specific elemental localization and speciation data will be useful in diverse fields.